Adam and Adamah: A Feminist Re-examination of Gender and Environment in the Yahwist’s Narrative - Uzoma Amos Dike (Perspectiva Teológica)
The Christian tradition of patriarchy often traces its roots to the Yahwist creation narrative in Genesis 2:21-25. The study asks a pivotal question: “Does the Yahwist creation narrative teach male primacy?" However, a closer examination of the Hebrew words "Adam" and "Adamah" suggests a more egalitarian relationship between man and woman. This study aims to re-examine the narrative using grammatical analysis and feminist hermeneutics to challenge the traditional interpretation of male headship. While some interpretations have been influenced by eisegesis, a careful analysis suggests that the Yahwist narrative does not explicitly advocate for male primacy. Instead, it presents a non-derogatory view of the feminine gender and emphasizes humanity’s responsibility to care for the earth. Hence, the study advocates for a reconsideration of male headship in the Christian traditions.